Dr. Paul F. Fortes — Deep Plane Facelift — Houston - Fortes, Paul F. (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Paul F. Fortes, practicing in Houston, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002979; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; houston